2006
DOI: 10.1111/j.1467-8659.2006.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Computing discrete shape operators on general meshes

Abstract: Discrete curvature and shape operators, which capture complete information about directional curvatures at a point, are essential in a variety of applications: simulation of deformable two-dimensional objects, variational modeling and geometric data processing. In many of these applications, objects are represented by meshes. Currently, a spectrum of approaches for formulating curvature operators for meshes exists, ranging from highly accurate but computationally expensive methods used in engineering applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…In doing so, after subdivision, our remeshings will all possess regular connectivity in the interior. Such regularity offers several advantages in computing local geometry features, e.g., curvatures [10]. Sec- ond, our mask covers the desired facial area with a substantially small number of markers.…”
Section: Maskmentioning
confidence: 99%
“…In doing so, after subdivision, our remeshings will all possess regular connectivity in the interior. Such regularity offers several advantages in computing local geometry features, e.g., curvatures [10]. Sec- ond, our mask covers the desired facial area with a substantially small number of markers.…”
Section: Maskmentioning
confidence: 99%
“…Figure 7 shows convergence rates under refinement for largely differing polygonal mesh types, indicating linear convergence in the L 2 sense. Grinspun et al [2006] have investigated the effect of different mesh types for bending problems using the cotan Laplacian. We share their observation that convergence behavior meliorates for irregular unstructured meshes and meshes with hexagonal symmetry, while it deteriorates for strongly anisotropic meshes.…”
Section: Thin Plate Bendingmentioning
confidence: 99%
“…A jet is a truncated Taylor expansion, and the incentive for using jets is that they encode all local geometric quantities such as normal, curvatures, extrema of curvature, while Razdan and Bae [19] introduced a method which is based on biquadratic Bezier patches as a local surface fitting technique for determining curvature, where it used for approximation of the neighborhood of mesh vertex for computation of curvature instead of taking the quadric analytical function approach. Grinspun et al [20] applied a simple shape operator formulation, using normals as degrees of freedom. They have observed that normals are represented in a natural way as scalars of edges, similar to 1-forms.…”
Section: Curvature Estimation On Triangulated Surfacementioning
confidence: 99%